ST Elevation in Lead aVR and Its Association with Clinical Outcomes - Eka Ginanjar; Yulianto Yulianto (Interna Publishing, 2018)
The purpose of this case repots are to evaluate the role of ST elevation in aVR lead and to make analysis between both cases. There are some atypical electrocardiogram (ECG) presentations which need prompt management in patient with ischemic clinical manifestation such as ST elevation in aVR lead. In this case study, we report a 68-year old woman with chief symptoms of shortness of breath and chest discomfort. She was diagnosed with cardiogenic shock, with Killip class IV, and TIMI score of 8. The second case is a 57-year-old man with typical chest pain at rest which could not be relieved with nitrate treatment. He was diagnosed with ST elevation in inferior and aVR lead, and occlusion in left circumflex artery (LCX). Both patients underwent primary percutaneous coronary intervention (PPCI). Subsequently, both cases presented remarkable clinical improvements and improved ST elevation myocardial infarction (STEMI) in aVR lead.